SOCIAL MEDIA AS AN INTEGRATIVE PLATFORM FOR PSYCHOLOGICAL TECHNIQUES IN MARKETING ARDHIFER FERTILIZER - Rijal Assidiq Mulyana (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study aim to explain the marketing landscape is undergoing a transformation driven by the rapid development of technology. Currently, the promotion of products and services is predominantly executed through social media, a shift compelled by changes in consumer behavior. In Indonesia, for instance, approximately 73.7% of the total population are social media users. This study aims to broaden the understanding of the effectiveness of social media platforms as digital marketing channels by incorporating psychological techniques in the context of sustainable business. Employing a qualitative method with an inductive approach, this research seeks to develop novel theories and concepts based on the presented data. The author’s focus on the psychology of digital marketing within sustainable business makes this study unique, as relatively few works have specifically addressed this domain. The findings indicate that TikTok Shop is considered superior due to its integration of social media and e-commerce functionalities. The cooperative leverages psychological factors, specifically social proof, loss aversion, anchoring, framing, and commitment, which are disseminated through posters and marketing videos. While all these psychological factors contribute to increased consumer purchase intention, commitment was found to have a comparatively smaller impact than the others.